Clinical presentation and spectrum of opportunistic infections among HIV patients encountered in coastal Karnataka, South India - Jutang Babat Ain Tiewsoh; Beena Antony (Journal of Family Medicine and Primary Care)
Background: Human immunodeficiency virus (HIV) affects the immune system, bringing the body’s defenses down resulting in the occurrence of opportunistic infections (OIs) which account for high morbidity and mortality. Aims: 1) To analyze the demographic pattern including age, sex, and marital status of HIV seropositive patients. 2) To investigate the clinical presentation, spectrum of OIs, and outcome of HIV-infected individuals. Settings and Design: Descriptive cross-sectional study. Methods and Material: The study was conducted for a period of two years. HIV status was determined following NACO guidelines. Patients of either sex and of any age found to be sero-positive for HIV were included in the study. Demographic information, clinical presentation, different OIs isolated, outcome and determination of CD4 count were recorded. Statistical Analysis Used: SPSS version 17-0. Results: A total of 137 infected individuals were included in the study, the most common presentation on admission was fever followed by gastrointestinal symptoms. Tuberculosis was the most common OI encountered followed by oral candidiasis. The CD4 count showed Tuberculosis having a median value of 162, Oral candidiasis 174, and Pneumonia 214, while others like PCP, Toxoplasma, CMV, Cryptococcus, and Herpes zoster presented with a median value of 96, 101, 369.5, 42, 299. Conclusions: Fever followed by gastrointestinal symptoms was the most common clinical presentation. Tuberculosis was the most common OI followed by oral candidiasis in patients infected with HIV but other infections were also encountered. Therefore, clinicians on diagnosis of HIV should keep in mind to screen for the common OIs and vice versa.